Dampak Layanan Go Food Dalam Meningkatkan Omzet Penjualan Pedagang Kuliner Halal Di Kecamatan Rangkasbitung - Eka Yoga Swara (e-Jurnal Aksioma Al-Musaqoh : Journal of Islamic Economics and Business Studies, 2020)
The Go-Food service is a food delivery service feature for food delivery that was developed by the Go-Jek application in March 2015 and expanded to Rangkasbitung at the end of 2019. Since the emergence of Go-Food in Rangkasbitung, it has received a positive response from consumers, making beginners and senior halal culinary entrepreneurs confused about how Go-Food will impact their business if they join Go-Food later, so this research was created by the author's idea.This study aims to determine the impact of Go-Food services for middle and lower entrepreneurs by taking a sample that looks at a fairly good rating of 4 stars and above on the Go-Jek application from its consumers so that researchers can obtain the data needed by researchers regarding the factor of decreased turnover, solutions to increase turnover, and the impact of Go-Food services on increasing sales turnover in Rangkasbitung District. This research was conducted so that entrepreneurs who have just started or have been around for a long time can determine good steps in making decisions about their business so that the desired targets can be achieved. This research was conducted at one of the restaurants that have joined the Go-Food service in Rangkasbitung District, namely Warung Duren Langlangbuana, where the owner of Warung Duren Langlangbuana is the only one who has the same criteria as the problem with researchers, namely not having a fixed location to sell but can remain compete in the market.This study uses a qualitative research method where data collection is carried out by interviews, book excerpts, and the internet so as to be able to dig deeper into the impact of the Go-Food Service. The research results obtained from this study state that online Go-Food services can increase sales turnover by 30% of the overall sales turnover at Warung Duren Langlangbuana. So it can be concluded that Go-Food services are quite influential in increasing sales turnover of halal culinary traders in Rangkasbitung District.Keyword : service, Go-Food, halal culinary